KAJIAN FAKTOR-FAKTOR PRODUKSI JERUK DENGAN REGRESI LINIER BERGANDA DI KABUPATEN KARO SUMATERA UTARA PADA TAHUN 2002-2021 - Ginting, Amalia; Nurviana; Fairus (JURNAL GAMMA-PI, 2025)
Karo Regency is recognized as one of the main citrus-producing regions in North Sumatra, contributing significantly to the local agricultural economy. However, citrus production in this area has fluctuated over the years, possibly due to variations in climatic conditions. This study aims to examine the extent to which climatic factors influence citrus production in Karo Regency. The analysis employed a multiple linear regression approach to identify the relationship between climatic variables and production outcomes. The research utilized secondary data obtained from relevant institutions, including citrus production records and climate data for the study period. Independent variables included temperature, humidity, rainfall, and the number of rainy days, while citrus production served as the dependent variable. The findings revealed that both jointly and individually, climatic factors had no significant effect on citrus production. The coefficient of determination (R²) of 0.211 indicates that only 21.1% of production variation is explained by the model. Consequently, future studies are encouraged to incorporate other determinants such as cultivation practices and farm management strategies